2009
DOI: 10.1097/hcr.0b013e3181b4cc41
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training Improves Oxygen Uptake Efficiency Slope in Patients With Chronic Heart Failure

Abstract: In CHF patients with IMW, IMT results in a significant increase in OUES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 11 publications
3
59
1
8
Order By: Relevance
“…In disagreement with current study results, the previous studies had provided enhancements of ventilatory efficiency after HII exercise program, results abide blended and disputable, with many researches showing particular marker enhancements, but no improvement in other variables [3,22]. No differences were found after training in slope of VE/VCO 2 and OUES in the present study.…”
Section: Resultscontrasting
confidence: 57%
“…In disagreement with current study results, the previous studies had provided enhancements of ventilatory efficiency after HII exercise program, results abide blended and disputable, with many researches showing particular marker enhancements, but no improvement in other variables [3,22]. No differences were found after training in slope of VE/VCO 2 and OUES in the present study.…”
Section: Resultscontrasting
confidence: 57%
“…Estudo no nosso meio demonstrou que a idade não influencia a resposta ao exercício 69 . Outros métodos de treinamento têm sido utilizados como o treinamento complementar de músculos inspiratórios que pode ser indicado naqueles pacientes com IC que apresentam fraqueza da musculatura respiratória (> 70% da pressão inspiratória máxima predita) [70][71][72] ; pilates 73,74 ; treino intervalado e contínuo 66,75,76 ; eletroestimulação 77 ; e hidroterapia 78,79 . Intensidades diferentes de exercício podem ter ação diferente na fisiopatologia da IC 80 .…”
Section: Reabilitação E Treinamento Físico (Tabela 10)unclassified
“…This allows for fitness and functional comparisons across different subject populations. Recent studies have shown that OUES is influenced by age, body size, and even the musculature of the secondary respiratory muscles (5,32,53,72). Additionally, the two variables comprising the OUES are known to be affected by metabolism; so it is possible that the OUES might vary by maturation as a function of muscle metabolism (14).…”
Section: Significance Of the Problemmentioning
confidence: 99%